2016
DOI: 10.1016/j.micres.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasmal lipoprotein p37 binds human protein HER2

Abstract: Mycoplasmas are a group of microbes that can cause human diseases. The mycoplasmal lipoprotein p37 promotes cancer metastasis, at least in part, by interacting with EGFR. In this study, we show that the p37 lipoprotein binds another member of the EGFR family, HER2, through the HER2 extracellular domain. The binding of p37-HER2 promotes phosphorylation of HER2 and activates the downstream signaling molecule Erk1/2. Because the HER2 signaling pathway contributes to breast tumor metastasis, our results imply that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…To further explore the underlying mechanisms in HCC cells, we analyzed the expression of molecules reported to interact with p37 9 , 22 , 23 , 24 , 25 in TFAM‐knockdown cells using RNA sequencing data. 14 As shown in Figure 4A , ANXA2 was the most upregulated gene at the mRNA level in HCC cells with TFAM knockdown.…”
Section: Resultsmentioning
confidence: 99%
“…To further explore the underlying mechanisms in HCC cells, we analyzed the expression of molecules reported to interact with p37 9 , 22 , 23 , 24 , 25 in TFAM‐knockdown cells using RNA sequencing data. 14 As shown in Figure 4A , ANXA2 was the most upregulated gene at the mRNA level in HCC cells with TFAM knockdown.…”
Section: Resultsmentioning
confidence: 99%
“…Mycoplasma hyorhinis membrane protein P37 is a functional protein intensively studied for its role in tumor behaviors[ 36 , 42 ]. ANXA2[ 43 ] and HER2[ 44 ] are two known binding sites of P37. Recent data indicated that P37 promoted tumor progression through its interaction with ANXA2 in host cells, while P37 antibodies, a polypeptide A2PP (a 30 amino acids polypeptide within the N-terminal of ANXA2), and anti-mycoplasma reagent like MYCO I, were able to block this interaction[ 16 ].…”
Section: Discussionmentioning
confidence: 99%